A case study in whole building energy modeling with practical applications for residential construction - Knuth, Cody William (Kansas State University, 2012)
An energy analysis was performed on a Midwestern residence to evaluate its performance based on energy use. A model of the actual house was replicated using eQuest and adjusted until its projected utility bills matched the actual yearly bills. This model was used to gauge how potential improvements made to the envelope and HVAC systems lowered the energy use. The results were documented after each improvement the feasible options were considered. The top alternatives were then combined to see how much money could be saved through renovating an existing home or through constructing a new residence. The overall goal of this report was to use the resulting improvement data as a reference for homeowners or home builders who are interested in conserving energy and money through residential improvements.
Keywords: Energy model; Residential envelope improvements; Residential system improvements; Energy analysis; Architectural engineering (0462)